EDUCATION WITH BOOKLETS MEDIA ON HIV PATIENTS IN THE HOSPITAL: A QUASI EXPERIMENTAL CLINICAL TRIAL - Apriliyani, Fitri; Akrom; Wijaya, Uniarti (Transpublika Publisher, 2022)
Regular visits of HIV patients to the hospital are expected to provide a positive therapeutic out-come because during the visit clinical monitoring, laboratory testing, counseling conducted by health workers and VCT themes, as well as taking antiretroviral (ARV) routine drugs every once a month, so that it is expected that the compliance of HIV patients to take ARV drugs will increase. Marking the success of the treatment of antiretroviral therapy come from HIV patients includes the minimum opportunistic infections related to AIDS and malignancy, increased CD4 cell counts, and increased body weight. The purpose of this study was to determine the effect of booklet media education on the level of adherence, perception, clinical out come and the quality of life of HIV patients in RSUD R. Soedjati Soemodiharjo The method used was quasi experimental with the design of two design pretest-posttest groups. Data were analyzed by univariate and bivariate. Statistical tests using a sample independent-sample test. The results obtained from this study are a description of the demographic characteristics of HIV patients in RSUD R. Soedjati Soemodiharjo, namely the highest age at 18-29 years as many as 22 patients (36%), dominated by women 43 people (70,5%), married as many as 49 people (80,3%), elementary school education 35 patients (57,4%), the most work was not working 23 people (37,8%), the highest duration of illness was above 1 year, 29 patients (47,6%), the most comorbid / comorbidities suffered by HIV patients in RSUD R. Soedjati Soemodiharjo were TB as many as 8 patients (36,4%). Perception on perception shows a P value of > 0,05. Intervention on compliance analysis results P > 0,05. Both treatment and control studies have moderate adherence because they have 48 patients (78,6%). Statistical results showed a significant difference for Hb because the SPSS results were P < 0,05 between the treatment with controls and for the leukocyte number P > 0,05, meaning that there was no significant difference between treatment and control. Interventions with quality of life P < 0,05. The conclusion is the influence of quality of life education intervention, Hb on HIV patients in RSUD R Soedjati between the control and treatment groups P <0,05.